Promising short-term clinical results of the cementless Oxford phase III medial unicondylar knee prosthesis - van Dorp, Karin B (World J Orthop, 2016)
AIM: To investigate the short-term clinical results of the Oxford phase III cementless medial unicondylar knee prosthesis (UKP) compared to the cemented medial UKP. METHODS: We conducted a cross-sectional study in a tertairy orthopedic centre between the period of May 2010 and September 2012. We included 99 medial UKP in 97 patients and of these UKP, 53 were cemented and 46 were cementless. Clinical outcome was measured using a questionnaire, containing a visual analogue scale (VAS) for pain, Oxford Knee score, Kujala score and SF-12 score. Knee function was tested using the American Knee Society score. Complications, reoperations and revisions were recorded. Statistical significance was defined as a P value < 0.05. RESULTS: In a mean follow-up time of 19.5 mo, three cemented medial UKP were revised to a total knee prosthesis. Reasons for revision were malrotation of the tibial component, aseptic loosening of the tibial component and progression of osteoarthritis in the lateral- and patellofemoral compartment. In five patients a successful reoperation was performed, because of impingement or (sub)luxation of the polyethylene bearing. Patients with a reoperation were significant younger than patients in the primary group (56.7 vs 64.0, P = 0.01) and were more likely to be male (85.7% vs 38.8%, P = 0.015). Overall the cementless medial UKP seems to perform better, but the differences in clinical outcome are not significant; a VAS pain score of 7.4 vs 11.7 (P = 0.22), an Oxford Knee score of 43.3 vs 41.7 (P = 0.27) and a Kujala score of 79.6 vs 78.0 (P = 0.63). The American Knee Society scores were slightly better in the cementless group with 94.5 vs 90.2 (P = 0.055) for the objective score and 91.2 vs 87.8 (P = 0.25) for the subjective score. CONCLUSION: The cementless Oxford phase III medial UKP shows good short-term clinical results, when used in a specialist clinic by an experienced surgeon.